Etika Medis Berbasis Tauhid Dalam Teknologi Reproduksi: Analisis Relasi Iman, Ilmu, Dan Amal Perspektif Bioetika Islam - Sri Sukmawati; Erlani; Ali Maulida (Yayasan Azhar Amanaa Yogyakarta, 2026)
The development of assisted reproductive technologies, particularly in vitro fertilization (IVF), offers hope for infertile couples to have children. However, this advancement also raises ethical issues concerning human intervention in the reproductive process, lineage status, human dignity, and the legitimacy of its use in Islam. Previous studies have generally examined reproductive technologies from the perspectives of fiqh law, maqāṣid al-sharī‘ah, or medical bioethics in a partial manner. Nevertheless, there remains limited research that specifically integrates the concept of Tawhid as a medical ethics paradigm through the relationship between faith, knowledge, and action in analyzing modern reproductive technologies. This gap forms the basis of the present study. This research aims to analyze the role of Tawhid as a foundation of medical ethics and to explain the relationship between faith, knowledge, and action as a framework of Islamic bioethics in responding to developments in assisted reproductive technologies. The study employs a library research method with a normative-philosophical approach and a conceptual research design. Data were obtained from 25 sources consisting of scientific articles, fatwas issued by Islamic institutions, and literature related to Islamic bioethics, infertility, IVF, gamete donation, surrogate motherhood, maqāṣid al-sharī‘ah, and Islamic medical ethics published during the 2021–2026 period. The data were analyzed using content analysis techniques through the identification, categorization, interpretation, and synthesis of Islamic bioethical concepts. The findings indicate that Tawhid functions as an ontological, epistemological, and axiological foundation in Islamic medical ethics. The relationship between faith, knowledge, and action serves as a regulatory mechanism to ensure that the use of reproductive technologies remains consistent with Sharia values. IVF is permissible when it uses sperm and ova from a legally married husband and wife without the involvement of a third party. In contrast, gamete donation and surrogate motherhood are rejected because they have the potential to compromise lineage and conflict with the principle of hifẓ al-nasl (preservation of lineage). This study produces a conceptual model of Tawhid-based reproductive bioethics as a guideline for ethical decision-making in contemporary medical practice.